Change in the Magnetic Domain Alignment Process at the Onset of a Frustrated Magnetic State in Ferrimagnetic La2Ni(Ni1/3Sb2/3)O6 Double Perovskite - Nieva, Gladys; Franco, D.G.; Carbonio, R.E.; Nieva, G. (IEEE (Institute of Electrical and Electronics Engineers), 2013)
Fil: Franco, D.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Instituto de Investigaciones en Físico-Química de Córdoba; Argentina; Universidad Nacional de Córdoba, Facultad de Ciencias Químicas; Argentina